PERSEPSI MAHASISWA UNTAG SURABAYA TERHADAP BUKU UU KIP - Kasih, Putri Cindra; Darmawan, Arif; Yulianti, Tri (representamen, 2015)
Research in Social and Political Science Student Perceptions title UNTAG Surabaya Against BookInformation Law dalah study aimed to determine the perception of Faculty of Social and PoliticalSciences, University August 17, 1945 Surabaya to guide the Public Information Act disclosure. This studyuses qualitative dheskriptif. From the research conducted, Student perceptions FISIP untag Surabaya tobook Act Public Information is Good Enough. It can be seen from the respondents that many argue thatthe Freedom of Information Law is good enough, but there is also a state well and there are states lessgood. From the research that has been obtained, the advice given to the government legislator socializeKIP this Act and the sanctions that are applied more to be addressed again.Keywords: Perception, Student, Book Law Public Information